Peran KKN dalam Meningkatkan Literasi Ekonomi Syariah di Kalangan Pelaku Usaha Kecil Desa Pahang Kecamatan Talawi - Aulia Syahfitri; Maysa Chairani; Imsar Imsar; Miratul imaniah; Nurhidayah Nurhidayah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
The Community Service Program (KKN) is one of the implementations of the university’s tridharma focused on community engagement, aiming to improve welfare and economic empowerment in rural areas. This study aims to analyze the role of the KKN program in enhancing Islamic economic literacy among small business owners in Pahang Village, Talawi District. The research employs a descriptive qualitative method using a participatory approach, involving KKN students, small entrepreneurs, and village officials as key informants. Data were collected through field observations, in-depth interviews, and documentation of activities. The results show that socialization, Islamic financial training, and business mentoring activities successfully improved participants’ understanding of Islamic economic principles such as honesty, justice, and the prohibition of usury. Moreover, the KKN program encouraged entrepreneurs to apply sharia-compliant transactions and develop sustainable financial management practices. Therefore, the KKN program has a significant contribution to strengthening Islamic economic literacy and fostering a small-business ecosystem rooted in Islamic values at the village level.